2012
DOI: 10.1038/nature10852
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms govern cardiac repolarization and arrhythmogenesis

Abstract: Sudden cardiac death exhibits diurnal variation in both acquired and hereditary forms of heart disease 1, 2, but the molecular basis is unknown. A common mechanism that underlies susceptibility to ventricular arrhythmias is abnormalities in the duration (e.g. short or long QT syndromes, heart failure) 3-5 or pattern (e.g. Brugada syndrome) 6 of myocardial repolarization. Here we provide the first molecular evidence that links circadian rhythms to vulnerability in ventricular arrhythmias in mice. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
269
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(297 citation statements)
references
References 27 publications
19
269
0
5
Order By: Relevance
“…It is certainly possible that I A densities are altered in SCN neurons as a result of circadian regulation of the transcripts encoding critical accessory or regulatory proteins. Interestingly, and consistent with the hypothesis that accessory subunits could play a critical role, it was recently reported that the circadian regulation of Kv4.2-encoded I to,f channels in mouse ventricular myocytes reflects circadian changes in the accessory Kv channel interacting protein, KChIP2, not in the Kv4.2 ␣ subunit (Jeyaraj et al, 2012). Alternatively, post-transcriptional mechanisms, such as changes in Kv ␣ subunit protein expression, localization and/or degradation, or altered interactions with other Kv ␣ subunits, accessory subunits, or other regulatory proteins (Covarrubias et al, 2008; could mediate circadian changes in I A densities in SCN neurons.…”
Section: Circadian Locomotor Activity Is Altered In Kv14mentioning
confidence: 66%
“…It is certainly possible that I A densities are altered in SCN neurons as a result of circadian regulation of the transcripts encoding critical accessory or regulatory proteins. Interestingly, and consistent with the hypothesis that accessory subunits could play a critical role, it was recently reported that the circadian regulation of Kv4.2-encoded I to,f channels in mouse ventricular myocytes reflects circadian changes in the accessory Kv channel interacting protein, KChIP2, not in the Kv4.2 ␣ subunit (Jeyaraj et al, 2012). Alternatively, post-transcriptional mechanisms, such as changes in Kv ␣ subunit protein expression, localization and/or degradation, or altered interactions with other Kv ␣ subunits, accessory subunits, or other regulatory proteins (Covarrubias et al, 2008; could mediate circadian changes in I A densities in SCN neurons.…”
Section: Circadian Locomotor Activity Is Altered In Kv14mentioning
confidence: 66%
“…Mining this database can help to understand or explain tissue‐specific circadian physiology. For instance, CCGs in the murine heart are involved in cardiac glucose and fatty acid metabolism (e.g., Dgat2 , Adpn , Ppp1cc 32), but also electrophysiology which results in oscillatory contractile properties 33 (e.g., Tcap 34 , Kv4.2, and KChIP2 35). Surprisingly, the cardiac‐specific clock not only drives rhythmic output under normal physiological conditions, but also under pathophysiological conditions as noted by its oscillating responsiveness to myocardial infarction mediated by oscillating phosphorylated Akt and GSK‐3 levels 36.…”
Section: Tissue‐specific Circadian Clocks Influence Organ Physiologymentioning
confidence: 99%
“…Signals known to drive nutrient catabolism, such as glucocorticoids (52,53) and cAMP-response element-binding protein activation (54), have been shown to induce KLF15 expression, whereas anabolic signals, such as insulin, can suppress its expression (55). In addition, we have recently demonstrated that cardiac KLF15 expression is directly regulated by BMAL1 (27), a central component of the mammalian circadian clock. Therefore, it is likely that balance between such catabolic and anabolic upstream signals, with additional synchronization via the circadian clock, regulates cardiac KLF15 function.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Given the intense interest in the interplay between lipid and branched chain amino acid metabolism during physiological and pathophysiological states (56), it will be interesting to explore whether these aspects of KLF15 function are perturbed in heart failure and other cardiometabolic diseases. Our current work in cardiac metabolism is also interesting to consider alongside our recent observation that KLF15 regulates cardiac repolarization in vivo (27). Studies in large animal models of heart failure demonstrate that regional electromechanical dyssynchrony is associated with profound changes in genes critical for myocardial lipid and amino acid metabolism (57).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 1 more Smart Citation